2017
DOI: 10.1186/s13063-017-2034-0
|View full text |Cite|
|
Sign up to set email alerts
|

Avoidable waste related to inadequate methods and incomplete reporting of interventions: a systematic review of randomized trials performed in Sub-Saharan Africa

Abstract: BackgroundRandomized controlled trials (RCTs) are needed to improve health care in Sub-Saharan Africa (SSA). However, inadequate methods and incomplete reporting of interventions can prevent the transposition of research in practice which leads waste of research. The aim of this systematic review was to assess the avoidable waste in research related to inadequate methods and incomplete reporting of interventions in RCTs performed in SSA.MethodsWe performed a methodological systematic review of RCTs performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(55 reference statements)
3
6
0
Order By: Relevance
“…14,2123 The fraction of trials at low risk of bias is similar to prior estimates. 8,24,25 Our estimate for the fraction of studies fulfilling reporting requirements (90.0%) is in line with prior studies that evaluated both ClinicalTrials.gov results deposition and publication, 26,27 both of which were deemed acceptable means of results reporting in our study. To our knowledge, our study is the first to apply these conditions jointly to a sample of trials, in addition to assessing importance via citation in clinical synthesizing documents.…”
Section: Discussionsupporting
confidence: 87%
“…14,2123 The fraction of trials at low risk of bias is similar to prior estimates. 8,24,25 Our estimate for the fraction of studies fulfilling reporting requirements (90.0%) is in line with prior studies that evaluated both ClinicalTrials.gov results deposition and publication, 26,27 both of which were deemed acceptable means of results reporting in our study. To our knowledge, our study is the first to apply these conditions jointly to a sample of trials, in addition to assessing importance via citation in clinical synthesizing documents.…”
Section: Discussionsupporting
confidence: 87%
“…These deficiencies may lead to bias in reported measures of effect estimates and inaccurate conclusions. These are not isolated findings, as previous studies focusing on the quality of reporting SAMs [1,16,17,19,20], observational studies [63,64] and even clinical trials [22,65,66] Fig. 2 Trend of the annual number of papers using SAMs from 2010 to 2019.…”
Section: Discussionmentioning
confidence: 72%
“…All reviews identified significant deficiencies in reporting SAMs including non-reporting of sample size estimation and testing of the PH assumption in the CPH regression models. In addition, there have been reports of inadequate and incomplete reporting of randomized trials and studies on infectious diseases without statisticians/epidemiologists in Africa [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication [ 1 ] the last sentence in the last paragraph under ‘Perspectives and implications’ in the Discussions section needs to be removed. The correct version can be found in this Erratum.…”
Section: Correctionmentioning
confidence: 99%